Interaction of a recombinant form of apolipoprotein[a] with human fibroblasts and with the human hepatoma cell line HepG2 - S P Tam; X Zhang; M L Koschinsky (Journal of Lipid Research, 1996)
We have studied the binding, uptake, and degradation of a recombinant form of apolipoprotein[a] (r-apo[a]) using a cultured cell model. In HepG2 cells and in human fibroblasts, r-apo[a] complexed with low density lipoprotein(LDL) is bound and internalized via high affinity (Kd = 10 nM) receptors; in both cell types, low affinity (Kd = 200-300 nM) sites also mediate free apo[a] uptake. Using competition studies, we found that the high affinity binding component corresponds to the LDL receptor. Involvement of the LDL receptor in r-apo[a] uptake by fibroblasts was confirmed using fibroblasts derived from an individual homozygous for familial hypercholesterolemia; in contrast to normal fibroblasts, these cells lacked the high affinity r-apo[a] binding component. Cell association of 125I-labeled r-apo[a] was increased and decreased concomitantly with the up- and down-regulation of the LDL receptor in response to a number of compounds. The addition of alpha 2-macroglobulin as well as treatment with heparinase, chondroitinase ABC, and sodium chlorate did not decrease total specific binding of r-apo[a], suggesting that neither the low density lipoprotein receptor-related protein nor cell surface proteoglycans are involved in r-apo[a] clearance. The low affinity binding component present in both fibroblasts and HepG2 cells likely corresponds to the plasminogen receptor, as binding of r-apo[a] to these sites was specifically decreased by the addition of plasminogen or the lysine analogue epsilon-aminocaproic acid, but not by the addition of tissue-type plasminogen activator. Heparin abolished uptake of r-apo[a] by the LDL receptor component only; this indicates that apo[a] must be associated with LDL to be cleared by this receptor. In contrast, free apo[a] can be effectively cleared by the plasminogen receptor which may represent a significant route of clearance for free apo[a] in vivo.